Does the Internet Expand the Educational Gap Among Different Social Classes? The Protective Role of Future Orientation - Chen, Jing-Jing; Liu, Ming Fei (Frontiers in Psychology, 2021)
Amid the social background of China where the Internet has penetrated into every corner of adolescents' life, we concerned for the role of Internet usage in influencing the educational gap among social classes. We investigated the mediating role of Internet usage preference for entertainment in the relationship between the family socioeconomic status (SES) and adolescent's academic achievement, and explore the moderating role of future orientation in the relationship. A total of 614 junior high school students were recruited to complete a questionnaire survey, including questionnaires for family SES, Internet usage preference and adolescent future orientation. The results showed that: (1) the relationship between family SES and academic achievement were mediated by Internet usage preference for entertainment; (2) the indirect effect was moderated by future orientation, such that the negative association between family SES and Internet usage preference for entertainment was only indicated in adolescents with low future orientation; and (3) the direct association between family SES and Internet usage preference for entertainment was moderated by future orientation.